Investigation Myocardial Perfusion Scan Parameters and Walls Motion in Patients undergoing Cardiac Surgery - Mohammad Mehdi Movahedi; Hamidreza Arianfar; Mohammad Atefi; Ali Tavakoli Golpaygani; Farshid Gheisari; Tahereh Mahmoudi (Journal of Biomedical Physics and Engineering)
Background: Coronary heart disease the most prevalent form of cardiovascular disease, results from the blockage of blood flow through arteries. The Myocardial Perfusion Scan (MPS) is considered a non-invasive method to assess the heart condition and provides valuable information, such as End Diastolic Volume (EDV), End Systolic Volume (ESV), Ejection Fraction (EF), Lung to Heart Ratio (LHR), and Transient Ischemic Dilatation (TID).Objective: This study aimed to investigate changes in gated heart scan parameters to diagnose patients, who are candidates for heart surgery.Material and Methods: In this descriptive cross-sectional study, 40 patients who are candidates for heart surgery were enrolled to evaluate the relation between the parameters of the gated heart scan and the amount of ischemic area of the heart. After scanning the patients, TID, ESV, LHR, and EF and also the movements of the heart walls are examined and analyzed in these patients.Results: According to the results of the one-sample t-test showing a significant difference between the parameters, the results were within the normal range (P-value<0.0001). Additionally, all patients showed changes in cardiac output and wall movement issues. Conclusion: The evaluation of Myocardial Perfusion Scan (MPS) and gated heart scan parameters can provide an effective method for diagnosing patients who may require heart surgery.